(untitled) (European Journal of Marketing and Economics, 2019)
The purpose of the study was to examine how project implementation factors (provision of work-space facility, entrepreneurship training and promotion of products) influence the performance of Jua-kali Empowerment Programmes (JEP) in Nairobi County, Kenya. The study was rooted upon theory of constraints and system theory of organization. Both descriptive and correlational survey designs were used in executing the research inquiry. The targeted population was 327 beneficiaries of the JEP in Nairobi County. Using Krejcie and Morgan formula, a sample of 181 beneficiaries was selected. Both simple random sampling and purposive sampling were used to choose the sample elements. Data was gathered using structured questionnaires and informant interview guide. Descriptive statistics like percentages, arithmetic mean and standard deviation as well as inferential statistics regression analysis was used in data analysis. Pearson correlation analysis was used to test relationship between variables and regression analysis was applied in predicting the research model. The reliability of questionnaires was ascertained by Cronbach Alpha Coefficient of reliability (at 0.6668). Fisher (F) tested the research hypothesis at ?=0.05 whereby, R= 0.563, R2= 0.317, F (1,145) =5.192 at P=0.000-0.05. Therefore, the null hypothesis was rejected as there was enough evidence to conclude that project implementation factors have significant influence on the performance of Jua-kali Empowerment Programmes. Hence recommendations were made to the implementors of Jua-kali empowerment programmes to ensure that the programmes are not only need based but also implemented in an integrated and coordinated approaches for effective realization of projected deliverables.